THE ANALYSIS OF GROUP DIVISION IN THE THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) LEARNING MODEL - Nursyahadah; Alkhafi Maas Siregar (Universitas Negeri Medan, 2025)
This research objective (1) Find out the effect of the group division in the TAPPS learning model of students' ability to solve problems; (2) Determine the improvement of students’ problem-solving ability after group division in the TAPPS learning model is applied; (3) find out the effect of group division in the TAPPS learning model on students’ learning outcomes; (4) Determine the improvement in the students’ learning outcomes after group division in the TAPPS learning model applied. The subjects of this research were students at SMA Islam Al Ulum Terpadu Medan consisting of two classes. X MIA 1 consists of 28 students who will be divided into 3 group divisions with different numbers of members. X MIA 2, formed of 30 students will also be divided into 3 group divisions with different numbers of members. The type of research was a true experiment to determine the effect of group division in the TAPPS model for the subject. The data collection instrument used in this research consisted of a problem-solving test with 10 essay forms that had been validated by three experts. The data analysis techniques used in this study are quantitative. The results of this study (1) There is an effect of group division in the TAPPS learning model on students’ problem-solving ability on momentum and impulse topics. (2) The improvement can be seen from the one-way ANOVA that was used to see the significant difference in the average score between all pairs in the pretest and all pairs in the posttest. The p-value in both correctors is smaller than 0,05 (0,000 < 0,05) (3) There is an improvement in students’ problem-solving ability, to the improvement of students’ learning outcomes. (4) The improvement can be seen from the n-Gain test was used to see the difference between pretest and posttest final values in every group division. The interval of n-Gain between group divisions is 0,32 – 0,40. this value is included in the medium category, which is (0.30 ≤ n-Gain ≤ 0.70). so, based on these results, the group division in the TAPPS learning model can improve student learning outcomes on momentum and impulse topics. Keywords: Group Division; TAPPS Learning Model; students’ problem-solving ability, students’ learning outcomes